2021
DOI: 10.3390/ijerph18083861
|View full text |Cite
|
Sign up to set email alerts
|

A Web Survey to Evaluate the Thermal Stress Associated with Personal Protective Equipment among Healthcare Workers during the COVID-19 Pandemic in Italy

Abstract: The pandemic has been afflicting the planet for over a year and from the occupational point of view, healthcare workers have recorded a substantial increase in working hours. The use of personal protective equipment (PPE), necessary to keep safe from COVID-19 increases the chances of overheating, especially during the summer seasons which, due to climate change, are becoming increasingly warm and prolonged. A web survey was carried out in Italy within the WORKLIMATE project during the summer and early autumn 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 42 publications
1
32
1
Order By: Relevance
“…It is therefore no surprise that almost all healthcare workers (93% of healthcare workers) experienced heat strain symptoms during COVID-19 medical duties with PPE, and that this prevalence was significantly higher compared to similar medical duties without PPE (30% of healthcare workers). These findings reinforce initial observations from UK, Italy, Singapore and India [5][6][7] and emphasize the magnitude of PPE-induced heat strain among healthcare workers.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…It is therefore no surprise that almost all healthcare workers (93% of healthcare workers) experienced heat strain symptoms during COVID-19 medical duties with PPE, and that this prevalence was significantly higher compared to similar medical duties without PPE (30% of healthcare workers). These findings reinforce initial observations from UK, Italy, Singapore and India [5][6][7] and emphasize the magnitude of PPE-induced heat strain among healthcare workers.…”
Section: Discussionsupporting
confidence: 89%
“…For example, a survey distributed among British healthcare workers (n = 224) revealed that 93% of the respondents experienced multiple heat strain symptoms (i.e., thermal discomfort, headache, fatigue, excessive sweating), whereas 65% and 76% experienced that heat stress impaired their cognitive and physical performance, respectively [5]. Similar observations were made in healthcare workers (n = 356) from Singapore, India and Italy, as thirst, excessive sweating, exhaustion, and desire to go to comfort zones were often reported [6,7]. An important limitation of these studies is the lack of insight into the prevalence of these complaints in the pre-COVID era (i.e., during similar medical duties but without PPE), which hampers the interpretation of the data.…”
Section: Introductionmentioning
confidence: 56%
See 1 more Smart Citation
“…In this sense, the use of protective equipment increases the temperature of the body surface, and the sensation of heat and perspiration, as shown by different investigations [ 27 , 28 , 29 ], conditions the appearance of thermal stress in PPE users. Our research shows that both types of PPE cause an increase in the sensation of heat; however, it was higher in the PPE-Conv users than the PPE-PAPR users.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it was more meaningful to have the "neutral group" be included in the "comfortable group,” to compare the "comfortable group" and the "uncomfortable group." Because they felt comfortable or neutral, it showed that the PPE had almost no effect on their work, but the subjects in the "uncomfortable group" had heat stress after wearing PPE, resulting in physical and psychological effects and some symptoms [ [13] , [14] , [15] , [16] ]. The "uncomfortable group" was our main focus in this study.…”
Section: Methodsmentioning
confidence: 99%